Bitcoin, Uncertainty, and Internet Searches - Keramiyan, Matin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This thesis examines the predictive power of the Macroeconomic Uncertainty Index (MUI) with a horizon of one month and the volume of uncertainty-related online searches measured by Economic Uncertainty Related Queries (EURQ) on the Bitcoin returns. The sample includes 118 observations with monthly frequency and ranges from September 2010 to June 2020. In addition to the conventional methods, due to the presence of outliers and the departure from Gaussian assumptions; the quantile analysis framework was used to study the persistency of the shocks, the long-run relationships, and Granger causality among the variables. For this purpose, the quantile unit root test of Galvao (2009), the quantile cointegration test of Xiao (2009), and the Granger causality test in quantiles (Troster, 2016) were applied. The empirical findings highlight several vital points that lead to important policy implications. First, the variables display asymmetric behavior in response to the shocks along different conditional quantiles. Second, the Bitcoin-EURQ indicates different adjustment mechanisms towards long-run equilibrium in different quantiles. Third, the long-run and causal relationships between the series might be significantly different throughout the conditional distributions of the variables. Fourth, of particular interest, the findings provide evidence for the significant predictive power of the fluctuations in MUI and EURQ on Bitcoin returns, mostly in low and high quantiles. Implications of these findings for empirical researchers and Bitcoin investors are discussed in the conclusion section in detail. Keywords: Cryptocurrency, Bitcoin, Macroeconomic uncertainty, Internet search volumes, Economic uncertainty-related queries, Granger causality in quantiles.

ÖZ: Bu tez, bir aylık bir ufukla Makroekonomik Belirsizlik Endeksinin (MUI) tahmin gücünü ve Bitcoin getirileri üzerinde Ekonomik Belirsizlikle İlgili Sorgular (EURQ) tarafından ölçülen belirsizlikle ilgili çevrimiçi aramaların hacmini incelemektedir. Örneklem, Eylül 2010'dan Haziran 2020'ye kadar aylık frekans ve aralıklarda 118 gözlem içermektedir. Geleneksel yöntemlere ek olarak, aykırı değerlerin varlığı ve Gauss varsayımlarından sapma nedeniyle; şokların kalıcılığını, uzun dönemli ilişkileri ve değişkenler arasındaki Granger nedenselliğini incelemek için kantil analiz çerçevesi kullanıldı. Bu amaçla Galvao'nun (2009) kantil birim kök testi, Xiao'nun (2009) kantil eşbütünleşme testi ve kantillerde Granger nedensellik testi (Troster, 2016) uygulanmıştır. Ampirik bulgular, önemli politika çıkarımlarına yol açan birkaç hayati noktayı vurgulamaktadır. İlk olarak, değişkenler, farklı koşullu nicelikler boyunca şoklara yanıt olarak asimetrik davranış sergiler. İkincisi, Bitcoin-EURQ, farklı niceliklerde uzun vadeli dengeye yönelik farklı ayarlama mekanizmalarını gösterir. Üçüncüsü, seriler arasındaki uzun dönemli ve nedensel ilişkiler, değişkenlerin koşullu dağılımları boyunca önemli ölçüde farklı olabilir. Dördüncüsü, özellikle ilgi çekici olan bulgular, MUI ve EURQ'daki dalgalanmaların Bitcoin getirileri üzerindeki, çoğunlukla düşük ve yüksek niceliklerdeki önemli tahmin gücüne dair kanıt sağlıyor. Bu bulguların ampirik araştırmacılar ve Bitcoin yatırımcıları için etkileri sonuç bölümünde ayrıntılı olarak tartışılmaktadır. Anahtar Kelimeler: Kripto para, Bitcoin, Makroekonomik belirsizlik, İnternet arama hacimleri, Ekonomik belirsizlikle ilgili sorgular, Kuantillerde Granger nedenselliği.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Assoc. Prof. Dr. Korhan Gökmenoğlu Karakaya.
Keywords: Banking and Finance; Bitcoin--Monet--Digital currency; Cryptocurrency; Bitcoin; Macroeconomic uncertainty; Internet search volumes; Economic uncertainty-related queries; Granger causality in quantiles